Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.3989/gya.1999.v50.i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phenolic compounds extracted from sunflower seeds on native lipoxygenase activity

Abstract: RESUMENEfecto de los compuestos fenólícos extraídos de semillas de girasol sobre la actividad lipoxigenasa nativa.Se obtuvieron extractos de lipoxigenasa de semillas de girasol usando 12 mezclas de extracción diferentes, y se determinó la actividad lipoxigenasa y el contenido en compuestos fenólicos. Este último se llevó a cabo mediante medida de la relación de absorbancias a 320/280 nm. El análisis estadístico de los resultados para los extractos mostró una correlación entre la actividad lipoxigenasa y la rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Oilseeds also contain antioxidants but attracted less attention because they are less often directly consumed, except nuts. However, antioxidant activity and natural antioxidants have been reported in the seeds of canola (Naczk, Amarowicz, Sullivan, & Shahidi, ) and sunflower (Kubicka, Jędrychowski, & Amarowicz, ). Studies on antioxidant activity of halophyte seeds are not well documented.…”
Section: Resultsmentioning
confidence: 99%
“…Oilseeds also contain antioxidants but attracted less attention because they are less often directly consumed, except nuts. However, antioxidant activity and natural antioxidants have been reported in the seeds of canola (Naczk, Amarowicz, Sullivan, & Shahidi, ) and sunflower (Kubicka, Jędrychowski, & Amarowicz, ). Studies on antioxidant activity of halophyte seeds are not well documented.…”
Section: Resultsmentioning
confidence: 99%
“…2002). Water, methanol and ethanol separately or mixed are commonly used to extract phenolic compounds from plant materials (Kubicka et al. 1999; Zielinski and Kozlowska 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The solvent extraction (methanol, ethanol and acetone) and identification of antioxidant component from hulls, coats and peels have been reported recently (Shahidi et al. 1997; Kubicka et al. 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Both CGA and CA are known as effective antioxidants 17, 18. Kubicka et al 19 demonstrated that both these acids inhibit the lipoxygenase (EC 1.13.11.12) of sunflower seeds. Furthermore, CA has manifested an effective antioxidant action on sunflower seed oil oxidation at 100 °C and at 25 °C 20…”
Section: Introductionmentioning
confidence: 99%